Surface Molecular Tailoring Using pH-Switchable Supramolecular Dendron-Ligand Assemblies - Iqbal, Parvez (American Chemical Society, 2014)
[Image: see text] The rational design of materials with tailored properties is of paramount importance for a wide variety of biological, medical, electronic and optical applications. Here we report molecular level control over the spatial distribution of functional groups on surfaces utilizing self-assembled monolayers (SAMs) of pH-switchable surface-appended pseudorotaxanes. The supramolecular systems were constructed from a poly(aryl ether) dendron-containing a dibenzo[24]crown-8 (DB24C8) macrocycle and a thiol ligand-containing a dibenzylammonium recognition site and a fluorine end group. The dendron establishes the space (dendritic effect) that each pseudorotaxane occupies on the SAM. Following SAM formation, the dendron is released from the surface by switching off the noncovalent interactions upon pH stimulation, generating surface materials with tailored physical and chemical properties.